Interpretasi Kualitatif Metode Gravitasi Studi Kasus Kawasan Gunung Merapi - Syifaalda Fitra; Syifa Chofifa; Denisya Berliana; Pandam Irmayanti; Firdha Kusuma Ayu Anggraeni; Sri Astutik (JFT: Jurnal Fisika dan Terapannya, 2023)
Mount Merapi is the highest volcano in Indonesia with an altitude of 2978 meters above sea level. Administratively, Mount Merapi is located in Magelang Regency, Central Java Province. The study was conducted related to the separation of regional anomalies and residual anomalies using gravity data for the case of Mount Merapi. This research was conducted with the aim of being able to interpret the subsurface structure at the location around the measurement. The second-order polynomial method is used in this study in addition to the separation of the Bouguer anomaly. The results of data processing obtained obtained very low anomaly results, which illustrates the presence of molten magma in the measurement area. In addition, there is a very high anomaly value which describes the presence of eruptive material originating from Mount Merapi.